Autopercepção do envelhecimento, autoimagem corporal, autopercepção de saude e morbidades prevalentes em idosos - Rocha, Laura Maria Brenner Ceia Ramos Mariano da (2014)
Self Perception of aging is a good indicator of successful aging. Studies on perception of aging have shown that a young subjective age and a high satisfaction with aging are associated with good health, high levels of wellbeing and few medical symptoms. The Aging Perception Questionnaire (APQ) is composed by 32 questions and evaluates self-perception of aging from distinct domains involving opinions about one s own aging process. There is no such a scale in Brazil up to date. The validation process of the APQ was performed with a sample of 402 individuals, from 60 to 104 years of age (68,3 ±7,4), specially women(59,2%). Confirmatory factor analysis demonstrated good adequacy of the Brazilian instrument .The internal consistency of the original data, presented an index of 0.889, indicating that the sample size is adequate for the application of the technique. The internal consistency of each dimension was also observed ranging from 0.555 to 0.831. The positive control and positive consequences were the dimensions that stood out in this population, with statistically significant values (p < 0.001), reflecting the perception of individuals to aggregate positive aspects and to have control over their own aging. Diabetes mellitus and depressive mood showed statistically significant levels when associated with the APQ.Body image satisfaction can influence behavior of individuals improving their performance in physical and social terms. On the other hand, physical disabilities resulting from aging also affect the perception of body image. Body satisfaction was observed in this work through the Stunkard Nine Figure Scale , in which individuals choose the figure that look more like his/her actual body image and the figure he/she believes that more closely resembles his/her ideal body image . A difference between the two figures demonstrates dissatisfaction with body image. Most respondents (67.2 %) reported being dissatisfied with their body image. The presence of obesity was significantly associated with body dissatisfaction (p<0,001), as well as depressive mood. There was also a trend towards a significant association with the presence of hypertension (0.087) and DM (0.056). In the analysis of the perception of aging and satisfaction with body image there is evidence that the group not satisfied with their body image is more inclined to believe that aging has a negative impact on their life. Self perceived health status was determined by a simple question (In general, how do you consider your health). In this sample, the majority reported having regular health (54.8 %) and only 6.1 % said they have great health. There was a significant association between perception of poor/bad health with the presence of DM, where 41.9 % (n = 13) of the individuals with this perception had DM (p < 0.05). There was also a relevant relationship with poor / very poor perception of health with obesity (p < 0.05), cardiovascular disease (p <0.05) and depressive mood (p < 0.001). In the analyses of the relationship between perception of aging and self perceived health, individuals with poor / bad and good / fair health appeared more inclined to believe that getting older makes it harder in their lives, compared to the group with great health perception.